1992
DOI: 10.1071/ch9920249
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic-Studies on Tajixanthone and Shamixanthone, Polyketide Hemiterpenoid Metabolites of Aspergillus variecolor

Abstract: The biosynthesis of tajixanthone and related metabolites of Aspergillus variecolor has been studied by incorporation experiments with simple and advanced precursors labelled with the stable isotopes 13c, 2~ and 180. Tajixanthone is shown to be derived through ring cleavage of an octaketide-derived anthraquinone with introduction of two dimethylallyl moieties. From the results of isotopic labelling experiments and chemical studies on model compounds, an overall biosynthetic pathway is proposed and information o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 0 publications
1
38
0
Order By: Relevance
“…3. In agreement with this, previous studies have reported arugosins to be precursors for emericellin (10) and shamixanthones (11) and (12) (Ahmed et al, 1992;Kralj et al, 2006;Márquez-Fernández et al, 2007), but have not established a genetic link to mpdG.…”
Section: Mdpg Is Involved In the Biosynthesis Of Arugosinssupporting
confidence: 70%
“…3. In agreement with this, previous studies have reported arugosins to be precursors for emericellin (10) and shamixanthones (11) and (12) (Ahmed et al, 1992;Kralj et al, 2006;Márquez-Fernández et al, 2007), but have not established a genetic link to mpdG.…”
Section: Mdpg Is Involved In the Biosynthesis Of Arugosinssupporting
confidence: 70%
“…Numerous polyhydroxy anthraquinones, including emodin, versicolorone, tajixanthone, and 1,3,6,8-tetrahydroxyanthraquinone, have been isolated from various Aspergillus species as secondary metabolites (1,8,43,46). All of these materials have similar chelated and phenolic hydroxyl resonances, as well as aromatic proton resonances.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we have shown that A. nidulans produces emericellin, shamixanthone, dehydroaustinol, and ergosterol peroxide during development in solidphase medium and that CfwA/NpgA is needed for the production of these compounds. Based on chemical structure and xanthone biosynthesis in A. variecolor (3,4), the xanthone emericellin can be synthesized from an anthrone precursor through a pathway involving at least one PKS. Shamixhantone may be formed by cyclization of one of the emericellin isoprenylated chains.…”
Section: Discussionmentioning
confidence: 99%